Developing a post-stroke home care checklist for primary care professionals in Turkey: a modified Delphi study - ÇİFÇİLİ, SALİHA SERAP; APAYDIN KAYA, MEMNUNE ÇİĞDEM (My University, 2023)
Aim: The aim of this study is to develop a post-stroke home care checklist for the use of primary care professionals. Background: Home care is an integral part of primary health care. In the literature, several scales are available to help determine elderly individuals’ need for home care services; however, there are no standard care criteria or guidelines for the home care of stroke survivors. Therefore, a standardized post-stroke home care tool specific for use by primary care professionals is needed to identify patients’ needs and to detect intervention areas. Methods: This is a checklist development study carried out between December 2017 and September 2018 in Turkey. A modified Delphi technique was used. In the first stage of the study, a literature review was carried out, a workshop was conducted with healthcare specialists in the stroke area, and a 102-item draft checklist was created. In the second stage, two written Delphi rounds were carried out via email with 16 healthcare professionals providing post-stroke home care. In stage three, the agreed items were reviewed, and similar items were grouped together to create the final checklist. Findings: A consensus was achieved in 93 of the 102 items. The final checklist, consisting of four main themes and 15 headings, was created. The four main areas of assessment in post-stroke home care are ‘assessment of current status’, ‘identification of risks’, ‘evaluation of the care environment and caregiver’, and ‘planning follow-up care’. The Cronbach alpha reliability coefficient of the checklist was found to be 0.93. In conclusion, the PSHCC-PCP is the first checklist created to be used by primary care professionals in post-stroke home care. However, it needs to be assessed in terms of effectiveness and usefulness with further studies.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); checklist; Delphi technique; elderly; home care; primary care; stroke